1990
DOI: 10.1002/bdd.2510110306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dose and sex on the pharmacokinetics of piroxicam in the rat

Abstract: The effects of dose and sex on the pharmacokinetics of piroxicam were studied in the rat. Piroxicam was administered intravenously at doses of 0.50 and 5.0 mg kg-1 to male and female rats. Plasma drug concentrations were determined by a highly sensitive high-performance liquid chromatographic technique. Non-compartmental pharmacokinetic parameters were calculated by area/moment analysis. A prolonged terminal half-life averaging 13.3 h in male rats and 40.8 h in female rats was observed. Dose had no effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The half-life of LMWH is about 2-4 h [4], but it has a fibrinolytic effect which lasts about 24 h at the application area [10]. One of the studies, which investigated pharmacokinetics of piroxicam, found that piroxicam had a 40.8 h half-life in female rats [22]. Due to the fact that piroxicam has a longer half-life than LMWH, it may have a longer effectiveness than LMWH.…”
Section: Discussionmentioning
confidence: 96%
“…The half-life of LMWH is about 2-4 h [4], but it has a fibrinolytic effect which lasts about 24 h at the application area [10]. One of the studies, which investigated pharmacokinetics of piroxicam, found that piroxicam had a 40.8 h half-life in female rats [22]. Due to the fact that piroxicam has a longer half-life than LMWH, it may have a longer effectiveness than LMWH.…”
Section: Discussionmentioning
confidence: 96%